EFEKTIVITAS ALAT PENGERING DEHIDRATOR TENAGA LISTRIK SEBAGAI ALTERNATIF PENGERINGAN HASIL PERTANIAN SEREH WANGI - Sugiarto, Bambang; Mariska Aulia Putri, Indah; Nur Azizah, Isnaini; Wahyu Widayati, Tunjung (Universitas Pembangunan Nasional Veteran Yogayakarta, 2024)
Most drying processes in Indonesia still utilize heat from direct sunlight. However, this method is deemed less effective because it is very dependent on the intensity of sunlight (weather) and the time required tends to be long. A drying tool is needed as an alternative that can be used to save drying time. This research aims to determine the efficiency of electrically powered drying equipment using citronella as an agricultural product that is abundant and easy to find. The variables used in this research are material weight with variations of 10, 15, 20, 25, 30 grams and drying time with variations of 10, 15, 20, 25, 30 minutes. The test methods used were air content testing, drying rate testing, mass flow rate testing and drying equipment efficiency testing. The results of the tests that have been carried out, obtained optimal results for the citronella material, namely with a weight variation of 10 grams over a period of 5 hours with the lowest water content of 2%. The efficiency of the electric power dryer was obtained at 65.62%.